Assessment of Remediation Efficiency for Soils Contaminated with Metallic Mercury in Hydrocarbon Extraction Zones - Anna Król; Ewa Kukulska-Zając; Monika Gajec (Applied Sciences)
Reducing mercury emissions to individual environmental compartments is now a global priority. However, undefined industrial sectors still pose a risk for mercury pollution, including the extraction, processing, and transport of crude oil and natural gas. Mercury contamination in hydrocarbon extraction areas can occur around blocking and bleeding systems, gas pressure reduction and metering points, gas purification devices, and reservoir water separators. The soil mercury content depends on the quality of the extracted fuel and can vary widely. This article reviews methods for remediating mercury-contaminated soils, including washing, acid washing, thermal desorption, removal and disposal, and soil stabilization to convert mercury into less harmful forms. The main objective of the work was to present the results of a pilot process of soil remediation contaminated with metallic mercury conducted in an industrial area. This paper presented laboratory and field test results evaluating the efficiency of a pilot soil remediation method at an industrial facility. Mercury contamination at the site was localized, primarily around blocking and bleeding systems, with soil mercury levels ranging from 1.6 mg/kg to 1116 mg/kg. In 80% of the samples, the mercury levels were 2–8.5 times above the acceptable industrial soil limits. Speciation studies indicated that over 50% of the samples contained mercury capable of emissions. The remediation method involved stabilizing the mercury in the soil by adding sulfur, forming stable mercury sulfide (cinnabar). The post-remediation measurements showed significant reductions in mercury emissions to the air, demonstrating the effectiveness of the mercury immobilization procedure.